Seserahan Dalam Perkawinan Adat Betawi: Sejarah dan Makna Simbolis - Jenny Sista Siregar; Lulu Hikmayanti Rochelman (Jayapangus Press, 2021)
One of the series of Betawi traditional marriages is Seserahan. Seserahan is an event where the prospective groom gives things to the woman that has meaning. The purpose of this study is to provide a comprehensive description of Seserahan and its symbolic meaning. This study uses a qualitative method. Data were collected using observation and interviews with informants and continued by analyzing Symbolic Interaction theory. The findings in the field show that Seserahan has differences in terms of what is written in the Betawi marriage book which is written in general even though the purpose is the same. In Seserahan, the prospective groom gives Seserahan objects to the woman which are divided into three categories, namely Compulsory, Customary, and Sunnah (may or may not be implemented). Mandatory objects are symbols of the groom's seriousness towards a wife based on religion, Customary objects are symbols of strengthening the bonds of brotherhood which indicate the distinctive characteristics of Betawi culture, Sunnah objects are symbols of prosperity and gratitude to face the household. Seserahan is given as a form of husband's readiness to his wife, a form of appreciation and respect for women